PERSEPSI MASYARAKAT TERHADAP KEBERADAAN USAHA SAPI POTONG (Studi Kasus Masyarakat di Area Peternakan Bapak Mutarom Dusun Gendong, Desa Purworejo, Kecamatan Sanankulon, Kabupaten Blitar): PERSEPSI MASYARAKAT TERHADAP KEBERADAAN USAHA SAPI POTONG (Studi Kasus Masyarakat di Area Peternakan Bapak Mutarom Dusun Gendong, Desa Purworejo, Kecamatan Sanankulon, Kabupaten Blitar) - putra, satria putra (Program Studi Peternakan, 2026)
This study examines public perception of a beef cattle farm owned by Mr. Mutarom in Dusun Gendong, Blitar, focusing on its social, economic, and environmental impacts. Using a descriptive quantitative method, data were collected from 45 residents living within 200 meters of the farm through observation and Likert-scale questionnaires. The study explored both positive perceptions (employment, manure, meat supply, compensation) and negative ones (odor, pollution, flies). Results show generally favorable community views. While few felt directly helped through jobs, 15.55% benefited from manure, 35.55% from affordable meat, and 20% from compensation. Meanwhile, 93.33% reported no odor disturbance, 100% no water contamination, and 88.88% no fly issues. These findings suggest minimal environmental disruption. The farm is seen as well-managed, with proper sanitation and waste handling. Although economic benefits are limited, community attitudes are largely neutral to positive. The study concludes that the farm can be a model for sustainable livestock practices if it enhances local engagement and maintains environmental standards. This research provides valuable insights for farm owners and policymakers to improve the social acceptance and sustainability of livestock development. Keywords: Public perception, beef cattle farming, environmental impact, organic fertilizer, Dusun Gendong, Sanankulon, Blitar.